(untitled) (London, 1963)
This book is an authouritative axamination of the validity of the concept of "take off" and of the evidence regarding it drawn by the most expert authourities from the critical periods in the development of the major countries.
Keywords: Economic development,Industrialization,Phát triển kinh tế,Công nghiệp hoá